Pembelajaran IPS Berbasis Problem Based Learning (PBL) dengan Scaffolding untuk Siswa SMP/ MTs - Anindya Fajarini (Tarbiyatuna Kajian Pendidikan Islam, 2018)
Social science learning should be able to prepare the future generation that has the ability to communicate, clear and critical thinking ability, the ability to consider the moral facet of a problem, the ability to become a citizen responsibility, the ability to try to understand and tolerant of different views, the ability to live in a globalizing society, have an interest in life, to have the readiness to work, have intelligence in accordance with talent /minatnya, and have a sense of responsibility to the environment.The facts on the ground indicate that students are still not accustomed to learn to pour his thoughts, provide the solution of social problems that occur with its factual independently. Problem Based Learning (PBL) becomes an alternative model of learning that can train the students solve problems, however LBC has its disadvantages, namely students difficulties in the process of solving problems. Implementation of PBL should be accompanied by the presence of scaffolding elements tailored to the learning objectives to be accomplished in order for implementation to be effective.